The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14744/eej.2019.80774
|View full text |Cite
|
Sign up to set email alerts
|

Activated Irrigation vs. Conventional non-activated Irrigation in Endodontics – A Systematic Review

Abstract: INTRODUCTIONRoot canal irrigation plays a pivotal role in Endodontics, to facilitate instrumentation by lubrication, remove debris, microorganisms, smear layer and prevent apical debris packing. Irrigants exert their effects, by mechanical, chemical and biological actions (1). On the mechanical front, streaming forces are delivered to the canal walls. On the chemical front, the active components exert specific actions on the organic and inorganic debris. On the biological front, the antimicrobial action on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 50 publications
2
50
0
3
Order By: Relevance
“…Improvement and advances in irrigation systems and strategies may result in better adequate debridement and removal of remnants of pulp tissue than the conventional syringe irrigation (35,36) especially in root canal cleanliness of the DDC access cavity ''Truss'' access. This might be in close relation to insufficient generation of hydrodynamic shear stress by conventional syringe and needle irrigation (37,38) . In "activation/agitation" strategy there is no analysis was done to determine if the cleanliness of the pulp chamber and root canals of DDC access cavities can be improved by this methods.…”
Section: Discussionmentioning
confidence: 95%
“…Improvement and advances in irrigation systems and strategies may result in better adequate debridement and removal of remnants of pulp tissue than the conventional syringe irrigation (35,36) especially in root canal cleanliness of the DDC access cavity ''Truss'' access. This might be in close relation to insufficient generation of hydrodynamic shear stress by conventional syringe and needle irrigation (37,38) . In "activation/agitation" strategy there is no analysis was done to determine if the cleanliness of the pulp chamber and root canals of DDC access cavities can be improved by this methods.…”
Section: Discussionmentioning
confidence: 95%
“…The long-term survival of endodontic treatment is an issue of high priority focus in pediatric dentistry. The success of endodontic treatment depends on a number of factors including a good biomechanical shaping, disinfection, and three-dimensional filling of the root canal system (1)(2)(3). The mechanical instrumentation utilized for the purpose of cleaning and shaping the root canal system results in the formation of smear layer covering the walls of dentin that not only contains dentin residues, but also the remnants of odontoblastic processes, pulp remnants, as well as bacteria (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews compared PUI with SNI and ANP with SNI did not prove the superiority of these IAT in terms of outcome in Endodontic treatment ( 16 , 17 ). Recent systematic reviews based on in vitro studies reported cleaner canals and isthmi following mechanical activation ( 18 , 19 ). One of them concluded that mechanical activation can reduce post-operative pain ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews based on in vitro studies reported cleaner canals and isthmi following mechanical activation ( 18 , 19 ). One of them concluded that mechanical activation can reduce post-operative pain ( 18 ). In view of these findings, it will be interesting to know the current practices/trends of IAT amongst Endodontists, noting that survey studies available in the literature investigated the type and concentration of irrigants used by clinicians with no emphasis on the use of IAT ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%